Comprehensive analysis of senescence-related genes and immune infiltration in intervertebral disc degeneration: a meta-data approach utilizing bulk and single-cell RNA sequencing data - Deng, Ya-Jun; Wang, Xin-Gang; Li, Zhi; Wang, Bo; Li, Jie; Ma, Jun; Xue, Xiong; Tian, Xin; Liu, Quan-Cheng; Liu, Jia-Yuan; Zhang, Ying; Yuan, Bin (Frontiers in Molecular Biosciences, 2023)
Objectives: This study aims to identify the key senescence genes and potential regulatory mechanisms that contribute to the etiology of intervertebral disc degeneration (IDD).Method: We analyzed GSE34095 and GSE70362 datasets, identifying key senescence-related differentially-expressed genes (DEGs) in IDD using lasso regression. Risk scores classified patients into high-and low-risk groups. We compared pathways, functions, and immune infiltration between these groups. Diagnostic ability was assessed using ROC curves and a nomogram predicted IDD incidence. In single-cell dataset GSE165722, we evaluated expression of key senescence-related DEGs.Results: We identified 12 key senescence-related DEGs distinguishing high-and low-risk IDD patients. Enrichment analysis revealed cellular stress response, apoptotic signaling pathway, and protein kinase activation differences. Immune cell analysis showed elevated eosinophils in low-risk group and increased effector memory CD8 T, central memory CD4 T, myeloid-derived suppressor, natural killer, monocyte, Type 1 T helper, plasmacytoid dendritic, and natural killer T cells in highrisk group. A nomogram using AUC > 0.75 genes (CXCL8, MAP4K4, MINK1, and TNIK) predicted IDD incidence with good diagnostic power. High senescence scores were observed in neutrophils.Conclusion: Our diagnostic model, based on key senescence-related DEGs and immune cell infiltration, offers new insights into IDD pathogenesis and immunotherapy strategies.